Determination of Diclofenac Potassium in Human Plasma by LC-MS - BHANU PRAKSAH, T.; VIJAYA SRI, K.; RAMA KRISHNA, S. (Asian Journal of Chemistry, 2010)
A rapid and sensitive liquid chromatography-mass spectrometry (LC-MS) method has been developed and validated for quantification of diclofenac potassium in human plasma. The analyte was extracted from human plasma by simple precipitation technique. Bupropion was used as the internal standard. A kromasil C18 column provided chromatographic separation of the analyte which was followed by detection with mass spectrometry. The mass transition ion-pair was followed as m/z 296.10 and 214.10 for diclofenac 240.1 and 184.10 m/z for bupropion. The method involves precipitation of diclofenac from plasma, simple isocratic chromatography conditions with mobile phase acetonitrile: water and mass spectrometric detection that enables detection at nanogram levels. The retention times were 1.58 and 1.21 min for diclofenac and bupropion, respectively. The proposed method has been validated with linear range of 150-3181 ng mL for diclofenac. The precision and accuracy values are within ± 10 %. The overall recovery of diclofenac was 41.9 %.